2020
DOI: 10.1177/1010539520957846
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Secondhand Smoke and Mental Health in Korean Adolescents

Abstract: This study assessed secondhand smoke exposure among nonsmokers and examined its association with mental health in Korean adolescents. We used the 14th Korea Youth Risk Behavior Survey in 2018 to extract data and analyzed 60 040 adolescents through 3 secondhand smoke exposure categories: home, school, and public places. Mental health included stress, insufficient sleep, depressive symptoms, and suicidal ideation. Secondhand smoke exposure was reported at 23.0% for home, 20.0% for school, and 51.4% for public pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Overall, in 2019 the prevalence (on ≥1 day during the past 7 days) was 34.1% (95% CI 33.1%-35.2%) at home, which is higher than in the United States (25.3%, 95% CI 23.4%-27.3%), while the prevalence of exposure was similar on public transportation between the 2 countries (China: 23.4%, 95% CI 22.3%-24.4%; United States: 23.3%, 95% CI 21.4%-25.4%) [17]. The prevalence of exposure to secondhand smoke was 57.3% (95% CI 56%-58.6%) in public places and 63.2% (95% CI 62%-64.5%) in any place in 2019, which was higher than in many other countries [9,18,19]. In addition, nearly a quarter (24.7%, 95% CI 23.8%-25.7%) of adolescents were exposed to secondhand smoke in any place daily, one-tenth (12.4%, 95% CI 11.8%-13%) at home and one-fifth (18.7%, 95% CI 17.8%-19.5%) in public places.…”
Section: Principal Findingsmentioning
confidence: 88%
See 1 more Smart Citation
“…Overall, in 2019 the prevalence (on ≥1 day during the past 7 days) was 34.1% (95% CI 33.1%-35.2%) at home, which is higher than in the United States (25.3%, 95% CI 23.4%-27.3%), while the prevalence of exposure was similar on public transportation between the 2 countries (China: 23.4%, 95% CI 22.3%-24.4%; United States: 23.3%, 95% CI 21.4%-25.4%) [17]. The prevalence of exposure to secondhand smoke was 57.3% (95% CI 56%-58.6%) in public places and 63.2% (95% CI 62%-64.5%) in any place in 2019, which was higher than in many other countries [9,18,19]. In addition, nearly a quarter (24.7%, 95% CI 23.8%-25.7%) of adolescents were exposed to secondhand smoke in any place daily, one-tenth (12.4%, 95% CI 11.8%-13%) at home and one-fifth (18.7%, 95% CI 17.8%-19.5%) in public places.…”
Section: Principal Findingsmentioning
confidence: 88%
“…In the multivariable logistic regression analysis, adolescents were more likely to be exposed to secondhand smoke in the combined data set (2013-2014 and 2019) if they were in a higher school grade (ninth vs seventh grade: odds ratio [OR] 1.76, 95% CI 1.68-1.84), were boys (boys vs girls: OR 1.18, 95% CI 1.15-1.22), lived in an urban setting (urban vs rural: OR 1.10, 95% CI 1.01-1. 19), and were a current cigarette smoker (smoker vs nonsmoker: OR 6.67, 95% CI 5.83-7.62). These results were largely independent of survey year (2013-2014 or 2019; Table 5).…”
Section: Association Between Secondhand Smoke Exposure and Potential ...mentioning
confidence: 99%
“…The intensity of the effect of SHS exposure on PLEs varied according to smoking status, and the effect was greater for never‐smoking adolescents than smoking adolescents. One nationally representative sample of Korea surveyed associations between SHS and mental health among three types of smoking status adolescents (never smokers, former smokers and current smokers), and found that the effect of SHS exposure on stress and sleep deprivation was greatest for never smokers (Kim & Kim, 2020). High stress and insufficient sleep were found can exacerbate the occurrence and development of PLEs in adolescents (Mamah et al, 2021; Wang, Chen, Chen, Yang, et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Secondhand smoke was reported at an alarming rate of 94.4% in their everyday lives including 20.0% at school, 23.0% at home, and 51.4% for public places. The end of the study showed Korean adolescents have a higher chance of experiencing poor mental health issues from being exposed to secondhand smoke (24,25).…”
Section: Long Term Effectsmentioning
confidence: 96%